RANCANGAN DAN ANALISIS KELAYAKAN PEMENUHAN GIZI IBU HAMIL MELALUI APLIKASI MENU GIZI IBU HAMIL (AMEZI BUMIL) - Desi, Desi; Petrika, Yanuarti; Rafiony, Ayu; Dahliansyah, Dahliansyah; Ulfa, Mauliana (Media Penelitian dan Pengembangan Kesehatan, 2024)
Nutritional intake during pregnancy is crucial for the health of pregnant women and optimal fetal development. The Pregnancy Nutrition Menu Application (AMEZI BUMIL) was developed to ensure balanced nutritional intake. The research aims to analyze the Pregnancy Nutrition Menu Application (AMEZI BUMIL). This study uses the Research and Development (R&D) method to analyze the feasibility of AMEZI BUMIL. This Android application goes through the planning, validation, design revision, and testing stages. The educational media for the pregnancy nutrition menu application (AMEZI BUMIL) was validated by 6 competent nutrition experts and 3 competent IT media experts. Identifying the deficiencies of this application, the researchers conducted revisions based on the validation by media and content experts. The final stage in the product design is product testing, which was carried out by 10 pregnant women in the Telaga Biru Health Center area in Pontianak City. The sampling technique used purposive sampling with sample determination based on small group testing conducted on 10 individuals. This research collected primary data using questionnaires for validation and small-scale testing. Total assessment scores can be calculated using the Likert Scale formula. Data is presented descriptively, and results are presented in descriptive and tabular forms. This application achieves significant acceptance levels from users, healthcare professionals, and media experts, with positive ratings exceeding 80% for users and healthcare professionals and over 55% for media experts, indicating good suitability. This success reflects the potential for widespread public adoption of AMEZI BUMIL as it has met user expectations.